2023
DOI: 10.3390/f14010154
|View full text |Cite
|
Sign up to set email alerts
|

Early Diagnosis of Pine Wilt Disease in Pinus thunbergii Based on Chlorophyll Fluorescence Parameters

Abstract: As the most severe forestry quarantine disease in several countries, pine wilt disease (PWD) causes substantial economic losses and poses a significant threat to the forest ecosystem. It is necessary to find a rapid and sensitive method for the early diagnosis of the disease to control the development of the disease effectively. This paper investigated the effect of Bursaphelenchus xylophilus(the pinewood nematode; PWN)on the chlorophyll fluorescence kinetic curve (OJIP curve) and the parameters of needles usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…of active PS-II RCs (Joly et al, 2005;Eullaffroy et al, 2009;Panda & Sarkar, 2012). Ficus religiosa leaves with gall infestation also yielded comparable results (Bhatt et al, 2022d;Liu et al, 2023). With the penetration of infection, the antenna size of infested leaves enlarged and attempted to absorb more energy, so the ABS/RC and TR/RC increased with the disease manifested in the leaves (Table 1).…”
Section: The Accumulation Of Q Amentioning
confidence: 85%
See 1 more Smart Citation
“…of active PS-II RCs (Joly et al, 2005;Eullaffroy et al, 2009;Panda & Sarkar, 2012). Ficus religiosa leaves with gall infestation also yielded comparable results (Bhatt et al, 2022d;Liu et al, 2023). With the penetration of infection, the antenna size of infested leaves enlarged and attempted to absorb more energy, so the ABS/RC and TR/RC increased with the disease manifested in the leaves (Table 1).…”
Section: The Accumulation Of Q Amentioning
confidence: 85%
“…But the gall formation alters biochemical and biophysical responses which negatively affect plant growth and development. When the disease spreads, leaves start to dry up and shrink, which is an obvious sign of damage in photosynthetic machinery and chlorophyll degradation (Bhatt et al, 2022d;Bhatt & Soni, 2023;Liu et al, 2023). Chlorophyll fluorescence kinetics is an aid as an advanced fast, sensitive, and non-destructive tool for analyzing the photosynthetic performance of leaves of the stressed.…”
Section: Introductionmentioning
confidence: 99%
“…The results were consistent with previous studies. Some researchers observed a significant decrease in net light and rate, chlorophyll content, and stomatal conductance following PWN infection in pine trees, indicating that PWN may cause damage to the photosynthetic structure of pine needles ( Liu et al., 2023 ). In this study, a large number of down-regulated genes were enriched in photosynthesis (ko00195), photosynthesis-antenna proteins (ko00196) and carotenoid biosynthesis (ko00906) with high rich factors ( Figure 3C ), indicating that photosynthesis continued to be inhibited in P. sibirica seedlings after PWN inoculation.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, the use of OJIP-test showed that DIo/RC parameter is the best indicator for the diagnosis of Bursaphelenchus xylophilus that is a pinewood nematode (PWN) of Pinus thunbergia [85], suggesting that this method may assist in disease detection localized in other plant organs, such as roots. In other interaction, it was demonstrated that F v /F 0 , F 0 , F m , and ABS/RC parameters were useful for identifying the physiological changes produced by F. verticillioides infection in maize plants [86].…”
Section: Cf Tool To Study the Plant-pathogen Interactionmentioning
confidence: 99%